A RETROSPECTIVE STUDY OF OUR NINE YEARS OF EXPERIENCE WITH ABNORMAL PLACENTATION - RISK FACTORS AND PREGNANCY OUTCOMES - Zornitsa Buteva; Georgy Stamenov; Tihomir Totev (Peytchinski Publishing, 2023)
Purpose: Placenta previa and morbidly adherent placenta are life-threatening conditions that necessitate close monitoring during pregnancy and can result in increased ante- and intrapartum complications. This study aims to evaluate the frequency of placental disorders in our population, reveal the impact of the known risk factors on maternal morbidity, and study new predisposing conditions and their effects on pregnancy outcomes. Materials and Methods: We performed a single-centered retrospective study in which we analyzed 330 women diagnosed with abnormal placentation-placenta previa and placenta accreta spectrum (PAS). We included all the women that gave birth at Nadezhda Hospital, from March 2013 to August 2021. We processed the data using the chi-square test, Cramer's V test, and cross-section analysis. Results: The frequency of placenta previa in our population is higher than the worldwide reported data. We were unable to demonstrate the connection between previous uterine manipulations (c-section, D&C, operative hysteroscopy, etc.) and the occurrence of higher-grade placenta previa in our population. However, the more surgeries performed, the more complications during pregnancy and delivery occur (antepartum bleeding, increased blood loss, surgical management of postpartum hemorrhage, peripartum hysterectomy). Pregnancies following assisted reproductive techniques (ART) are at a three-times higher risk of placenta previa. Endometriosis determines a greater risk of developing an abnormally adherent placenta. Conclusion: More prospective studies need to be performed to define the exact risk factors for abnormal placentation that affect the Bulgarian population. A better understanding of the condition will lead to better management of higher-risk pregnancies, thus reducing maternal and fetal morbidity.